The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1186/1471-2458-11-211
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for the ADDITION-Plus study: a randomised controlled trial of an individually-tailored behaviour change intervention among people with recently diagnosed type 2 diabetes under intensive UK general practice care

Abstract: BackgroundThe increasing prevalence of type 2 diabetes poses both clinical and public health challenges. Cost-effective approaches to prevent progression of the disease in primary care are needed. Evidence suggests that intensive multifactorial interventions including medication and behaviour change can significantly reduce cardiovascular morbidity and mortality among patients with established type 2 diabetes, and that patient education in self-management can improve short-term outcomes. However, existing stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 53 publications
0
45
0
Order By: Relevance
“…Self‐efficacy to engage in more physical activity was measured by two items identical to the ones used in Griffin et al . (2011) and Kinmonth et al . (2008) ( r  =   .52; α   =   .67).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Self‐efficacy to engage in more physical activity was measured by two items identical to the ones used in Griffin et al . (2011) and Kinmonth et al . (2008) ( r  =   .52; α   =   .67).…”
Section: Methodsmentioning
confidence: 97%
“…All studies were conducted in England between 2001 and 2012 and included data on 2,511 participants. The main results or protocol papers of these five data sets are published (Godino et al ., 2012; Griffin et al ., 2011; Kinmonth et al ., 2008; Marteau, Aveyard, et al ., 2012; Watkinson, van Sluijs, Sutton, Marteau, & Griffin, 2010). The analyses reported in this paper are novel and have not been reported elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…The design and rationale for the ADDITION-Plus study have been reported previously (2002)(2003)(2004)(2005)(2006)(2007) [22]. In brief, ADDITION-Plus is a randomised controlled trial nested within the intensive treatment arm of the ADDITION-Cambridge study, which evaluated the efficacy of a facilitator-led, theory-based behaviour change intervention for recently diagnosed type 2 diabetes patients.…”
Section: Methodsmentioning
confidence: 98%
“…Full details of the intervention have been described previously (see ESM) [9]. In brief, the intervention was delivered by three female trained lifestyle facilitators, who were not part of the general practice team.…”
Section: Methodsmentioning
confidence: 99%
“…Full details are reported elsewhere [9]. Participants also completed the consequences and treatment control subscales (11 items) of the Illness Perception Questionnaire-Revised [31, 32] and a nine-item closed-response questionnaire covering basic knowledge of diabetes and its management [33].…”
Section: Methodsmentioning
confidence: 99%